Antioxidant and Renin-Angiotensin System Inhibitory Properties of Cashew Nut and Fluted-Pumpkin Protein Hydrolysates - Sunday A. Malomo; Ifeanyi D. Nwachukwu; Abraham T. Girgih; Atinuke O. Idowu; Rotimi E. Aluko; Tayo N. Fagbemi (Polish Journal of Food and Nutrition Sciences)
Antioxidant and renin-angiotensin system (RAS)-inhibitory protein hydrolysates derived from the enzymatic hydrolysis of cashew nut (CNP) and fluted pumpkin (FPP) proteins were investigated. The CNP and FPP hydrolysates (CNPH and FPPH) from pepsin or Alcalase treatments were subjected to membrane ultrafiltration using different MWCOs to obtain 10 kDa peptide fractions. Hydrolysis of protein isolates at similar enzyme levels allowed obtaining peptic hydrolysates with a lower degree of hydrolysis (46.7-48.0%) when compared to the Alcalase-produced hydrolysates (47.7-50.3%). Amino acid composition revealed that CNPH had 28% hydrophobic residues when compared to higher contents (32-35%) in the 3-10 kDa peptide fractions. In contrast, aromatic residues increased from 8% in the FPPH to 9-13% in the peptide fractions. The in vitro • OH and DPPH • scavenging activities were significantly (p<0.05) enhanced by ultrafiltration but potency was inversely related to peptide size. The ferric-reducing power was the highest for the <1 kDa CNPH (2.47) when compared to 1.33 for CNPH and other peptide fractions. Metal chelation ability was significantly (p<0.05) enhanced by ultrafiltration only for the CNPH with 21% compared to ~96% for the peptide fractions. ACE inhibition was significantly (p<0.05) lower for the Alcalase CNPH and peptide fractions (~87%) compared to ~92% of pepsin-CNPH. However, renin inhibition was significantly (p<0.05) increased by ultrafiltration from 45.7 and 62.1% to ~82.4 and 96.5% for FPPH and CNPH, respectively. We conclude that the strong antioxidant properties coupled with RAS inhibition make CNPH and FPPH as well as their low molecular weight peptides potential ingredients to formulate health-promoting foods.